Construction of an induccible vector containing marker gene - Nurul Ashikin, Mohamed Ali (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study concerns on understanding the function of inducible promoter that can controlled the expression in plant. The used of controllable promoter region permit a regulated of a foreign gene in plant. The cassette contain the induce promoter carry a maker gene (GUS and LUC) was constructed in pUC plasmid. This construct based on the alcR regulatOlY system from the fungus Aspergilus nidulans with the application of ethanol as inducer.